Measuring the efficiency of public spending in the Iraqi economy for the period 2006-2013 - موسى, محمد علي (Journal of Economics and Administrative Sciences, 2017)
In light of the limited sources of funding suffered by the Iraqi economy, it highlights the importance of enhancing the efficiency of public expenditure, and if the measurement of the efficiency of public expenditure and identify benchmarks first step of promoting efficiency, the adoption of scientific methods of analysis imperative in promoting the efficiency. Under this framework, the focus was on the methodologies used to measure the efficiency of public spending and supply analysis with trying statement strengths and weaknesses, and make use of it in the measurement of the efficiency of public spending in the Iraqi economy. As well as devise measurable indicators take into account the specificity of the Iraqi economy and the stage through which the enormous challenges it faces, and try to apply them to the Iraqi economy. With a proposal for a set of ideas and mechanisms, to be enlightened by the decision-makers to enhance the efficiency of public spending in Iraq. It was among the search that the relationship between public spending and macroeconomic variables reflect the wrong approach followed in fiscal policy, as well as in the preparation of the budget and the allocation of resources. And that it is necessary to manage the economy through a new vision based on a review of the allocation of financial resources and the adoption of a new methodology to measure the efficiency of public spending, taking into account the limitations of the data, identify indicators that reflect the specificity of the Iraqi economy, and then finding appropriate means to enhance the efficiency of public spending.